Pathways to different urban water futures: ‘silver baskets’ of sociotechnical solutions - Vanessa Speight; Joby Boxall (Environmental Research: Infrastructure and Sustainability, 2025)
The water sector needs advances in a range of thematic areas to deliver sustainable water systems in a future characterised by climate change, population growth, and ageing infrastructure. Individual innovations will not be enough to deliver the step-change required. A multitude of sociotechnical advances in water management exist, however the real innovation challenge lies in understanding and demonstrating how combinations of these solutions can be deployed to deliver resilient and adaptive urban water systems. These combinations, or ‘silver baskets’, need to be tailored to local needs and context and work synergistically with existing infrastructure. The scale at which the solutions will be deployed ranges from individual domestic applications to city-wide infrastructure, across potential water qualities ranging from black water for reuse and resource recovery to ultra-pure potable water. This paper describes the results from a structured set of workshops across five years with UK water sector stakeholders from more than 250 organisations to develop potential future scenarios and pathways towards each one for urban water systems. While there is value in the resulting ‘silver baskets’, arguably there is more value in building skills through the process of collectively envisioning future options, transition pathways and drivers, and understanding the range of possibilities and combinations to deliver sustainable water futures across an entire country’s water sector. The study concluded that all water futures lie on, and can be considered and planned for on, a continuum from centralised to decentralised, despite the variety and complexity of the pathways, contexts, situations and pressures leading to them.